Too late to come back? The paradox of being a 50-year-old 'early career' black female academic - Msimanga, A. (South African Journal of Higher Education, 2014)
Much of what is known about the experiences of black women in academia is from research in the developed world. Little is known about the experiences of black women at African higher education institutions (HEIs) and even less about the experiences of black women who experience career breaks. Using an auto-ethnographic approach I reflects on her attempts to balance the demands of her different roles as a black woman and an academic. In a narrative that explores the complex relationship of time, career and context, the author argues that the time of womanhood, blackness and motherhood in academia is out of joint. Finally, she considers some of the strategies and resources that enabled her entry, re-entry, survival and growth during the course of her stop-andstart academic career. The author hopes that her story may contribute to the ongoing debates about the challenges of and possibilities for late-entry female academics at HEIs.